Women and social reform in modern India : a reader - Sarkar, Sumit, 1939-; Sarkar, Tanika, 1949- (Ranikhet : Permanent Black : Bangalore : Distributed by Orient Longman, 2007)
Contributed articles on social reforms and status of women in 19th and 20th century India.
Includes bibliographical references.
Keywords: Women -- India -- Social conditions -- 19th century; Women -- India -- Social conditions -- 20th century; Social problems -- India -- 19th century; Social problems -- India -- 20th century; Social change -- India -- 19th century; Social change -- India -- 20th century; Women -- India -- Social conditions -- 19th century -- Sources; Women -- India -- Social conditions -- 20th century -- Sources